Evaluasi Program Dakwah dalam Perspektif Manajemen Dakwah: Kajian Teoritis terhadap Indikator, Prosedur, dan Faktor Penghambat - Saidah Saidah; Naila Nurul Ilmi; Isna Mutia Putri (Pusat Riset dan Inovasi Nasional, 2025)
In his research, the author focuses on three problem formulations, (1). What are the indicators used in evaluating the success of da'wah activities? (2). To what extent does the application of da'wah activity evaluation contribute to improving the quality of da'wah? (3). What are the supporting and inhibiting factors in the process of evaluating da'wah activities? This study uses qualitative research, namely research that aims to gain a deep understanding of (Implementation of Da'wah Activity Evaluation Aimed at Improving the Quality of Da'wah) Data collection techniques used in this study include: interviews, observations, and documentation. While the data analysis used is by using qualitative descriptive analysis using inductive techniques, namely data mining in the field, then data reduction and data presentation are carried out, then conclusions are drawn. The results of the study show that: Evaluation in da'wah communication provides an understanding that preachers (D'ai) need to assess and evaluate the communication process carried out. This aims to improve and increase the effectiveness of da'wah. Evaluation of da'wah activities is an important tool for improving the quality of da'wah communication. By conducting systematic evaluations, preachers can identify strengths and weaknesses in their approach, and adjust strategies to achieve better results in the future. Implementing effective evaluation and showing how evaluation can improve the overall success of the da'wah program.